Nutritional Status and its Associated Factors among Under Five Children in BhimtarofSindhupalchowk District Nepal - Gautam, Jyoti; Acharya, Rija (Birat Journal of Health Sciences, 2020)
Introduction: The nutritional status of an individual is often the result of many inter-related factors. It is a major public health problem in most of the developing countries and occurs prominently among under-five children. Nepal is also the one of the developing country where the prevalence of malnutrition is high. Objective: This study aimedtoassess the nutritional status and its associated factors among under-five children. Methodology: A descriptive cross-sectional study was conducted in Bhimtar Village Development Committee of Sindhupalchowk.Study conducted in Jan 27 2017 to Feb 8 2017 with the sample 115, self-constructed semi-structured interview schedule was used for data collection and nutritional status was assessed using anthropometric measurements. Descriptive (Frequency, Percentage, Mean, Standard Deviation) and inferential statistic (chi-square test) were used for data analysis. Results: Among total children 47% were stunted, 30.4% were underweight and 11.3% were wasted. Age of child, frequency of antenatal visit and age of mother at child birth had significant association with nutritional status of children. Conclusion: The study concludes that significant proportion of under-five children in Sindhupalchowk district were malnourished with stunting and wasting being pre-dominant form of malnutrition. Occurrence of malnutrition was slightly higher among male compared to female children. Child’s age, mother’s age during childbirth and completion of atleast four antenatal visits during pregnancy were found to be significantly associated with child’s nutritional status.